Pattern of road traffic accident in Kelantan (1997-2003) - Azmani; Mohamed Rusli A.; Aziz Al-Sufi Ismail; Hashim M (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2004)
Road traffic accidents (RTAs) are among the ten cause of death in Malaysia. If is a shocking fact that RTAs killed more people in other developing countries too, every year, than war and disease. More than 20 million people are severely injured or killed on the world5 roads each year. The aim of this study was to determine the mortality and morbidity pattern ofroad traffic accidentsfrom 1997 to 2003 in Kelantan. The retrospective study was conducted in which the relevant data were collected by reviewing the records on road traffic accident (RTA) from the year 1997 to 2003. The records included information about monthly data such as number oflatal and nonfatal accidents and distribution of accidents by year. Data gathered were input into SPSS version 11 and simple linear regression to explore the trend in data analysis. A total of 40,452 accidents were reviewed during seven years period (1997-2003). The numbers of non fatal accidents showed an increasing trend from 1998 to 2003 except 2001, decreased in trend. Kelantan experienced a continuous increase of fatal accidents from 1997 until 2000, followed by a fluctuation between 2001 and 2003. The numbers of fatal and nonfatal accident cases showed no pattern, but total cases for both accidents increased by months within the one calendar year. Road traffic accidents are still a major public health problem. There were no systematic and consistent seasonal pattern of the mortality and morbidity of accidents. There were significant increasing trend throughout the months for both fatal and nonfatal accident cases within one year calendar.